2013
DOI: 10.3109/10253890.2013.850670
|View full text |Cite
|
Sign up to set email alerts
|

High novelty-seeking rats are resilient to negative physiological effects of the early life stress

Abstract: Exposure to early life stress dramatically impacts adult behavior, physiology, and neuroendocrine function. Using rats bred for novelty-seeking differences and known to display divergent anxiety, depression, and stress vulnerability, we examined the interaction between early life adversity and genetic predisposition for high- versus low-emotional reactivity. Thus, bred Low Novelty Responder (bLR) rats, which naturally exhibit high anxiety- and depression-like behavior, and bred High Novelty Responder (bHR) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 95 publications
4
68
1
Order By: Relevance
“…In our previous study we evaluated the effects of MS on behavior and endocrine function in the selectively-bred Low (bLR) and High (bHR) responder rats [3]. These rats were bred from the Sprague-Dawley strain and show striking differences in their depressive- and anxiety-like behavior, with bLRs showing a profile similar to the WKY rats and bHRs resembling Wistar rats [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study we evaluated the effects of MS on behavior and endocrine function in the selectively-bred Low (bLR) and High (bHR) responder rats [3]. These rats were bred from the Sprague-Dawley strain and show striking differences in their depressive- and anxiety-like behavior, with bLRs showing a profile similar to the WKY rats and bHRs resembling Wistar rats [5].…”
Section: Discussionmentioning
confidence: 99%
“…While MS did not induce changes in the bLR/bHR behaviors on the OFT and FST, their endocrine responses were differentially impacted with the bLRs manifesting an augmentation of adrenocorticotropic hormone secretion in response to an anxiogenic stimulus (i.e. exposure to the light/dark box) and bHRs showing its blunting [3]. While beyond the scope of the current study, it will be important to determine the impact of MS on the HPA axis activity in the WKY and Wistar rats given that the activity of this system has the potential to shape to depression and anxiety [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that some behavioral phenotypes confer resilience; for example, high noveltyseeking rats are more resilient against maternal separation, and do not exhibit the typical negative behavioral and neuroendocrine consequences [54]. Others have found that epigenetic mechanisms mediate the variable effects of maternal separation on mice of different genetic backgrounds [55].…”
Section: Vulnerability and Resiliencementioning
confidence: 97%
“…For example, bLR rats also exhibit greater anxiety- and depressive-like behaviors following stressful experiences (i.e., Calvo et al 2011; Stedenfeld et al 2011). Relative to bHRs, bLRs exhibit a higher physiological stress response (e.g., stress-induced defecation; Clinton et al 2014) and an attenuated corticosterone response to mild stressors, which appears to be a function of greater glucocorticoid receptor expression in the hippocampus (Clinton et al 2008), a finding also reported in outbred HR/LR rats (Kabbaj et al 2000). These bHR-bLR differences in HPA activity likely influence the dopamine system (e.g., Rougé-Pont et al 1998), which, in turn, could alter the response to cocaine (i.e., absence of bLR cocaine sensitization, García-Fuster et al 2010) as well as stimulus-reward learning (Flagel et al 2010, 2011).…”
Section: Discussionmentioning
confidence: 75%